Formative evaluation of the telecare fall prevention project for older veterans - Saliba Debra; Amulis Angel; Miake-Lye Isomi M; Shekelle Paul G; Volkman Linda K; Ganz David A (BMC, 2011)
Abstract Background Fall prevention interventions for community-dwelling older adults have been found to reduce falls in some research studies. However, wider implementation of fall prevention activities in routine care has yielded mixed results. We implemented a theory-driven program to improve care for falls at our Veterans Affairs healthcare facility. The first project arising from this program used a nurse advice telephone line to identify patients' risk factors for falls and to triage patients to appropriate services. Here we report the formative evaluation of this project. Methods To evaluate the intervention we: 1) interviewed patient and employee stakeholders, 2) reviewed participating patients' electronic health record data and 3) abstracted information from meeting minutes. We describe the implementation process, including whether the project was implemented according to plan; identify barriers and facilitators to implementation; and assess the incremental benefit to the quality of health care for fall prevention received by patients in the project. We also estimate the cost of developing the pilot project. Results The project underwent multiple changes over its life span, including the addition of an option to mail patients educational materials about falls. During the project's lifespan, 113 patients were considered for inclusion and 35 participated. Patient and employee interviews suggested support for the project, but revealed that transportation to medical care was a major barrier in following up on fall risks identified by nurse telephone triage. Medical record review showed that the project enhanced usual medical care with respect to home safety counseling. We discontinued the program after 18 months due to staffing limitations and competing priorities. We estimated a cost of $9194 for meeting time to develop the project. Conclusions The project appeared feasible at its outset but could not be sustained past the first cycle of evaluation due to insufficient resources and a waning of local leadership support due to competing national priorities. Future projects will need both front-level staff commitment and prolonged high-level leadership involvement to thrive.